Significance of Linked Color Imaging for Predicting the Risk of Clinical Relapse in Ulcerative Colitis - Shuji Kanmura; Akihito Tanaka; Kazuki Yutsudou; Kosuke Kuwazuru; Fukiko Komaki; Yuga Komaki; Hiromichi Iwaya; Shiho Arima; Fumisato Sasaki; Shiroh Tanoue; Shinichi Hashimoto; Akio Ido (Gastroenterology Research and Practice)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease with unknown etiology. Recently, mucosal healing has emerged as an important therapeutic endpoint in UC. Linked color imaging (LCI) is a novel endoscopic system that enhances the color differences of the gastrointestinal mucosa. Our previous study emphasized the redness and yellowness of the lesion using LCI observation, which was useful for the evaluation of histological mucosal activity in UC. In this study, we aimed to evaluate the correlation between LCI observation and clinical relapse rate in UC patients. We retrospectively analyzed UC patients who underwent total colonoscopy between August 2016 and October 2018 at our facility with Mayo endoscopic scores of 0 or 1. We assessed the correlation between orange-like color lesion (defined as LCI-scarlet color lesions) and clinical relapse rate (requiring additional treatment for UC) during the 1-year follow-up period. Fifty-eight patients (22 female, 36 male; median age at diagnosis, 47.2 (18–80) years) who underwent colonoscopy were analyzed. During the 1-year follow-up period, clinical relapse was observed in 12 patients (20.1%) among which ten patients (83.3%) had an LCI-scarlet color lesions recognized by LCI. By contrast, 29 patients (63%) had no LCI-scarlet color lesions in the clinical remission group (n=46). There was a significant difference in LCI-scarlet color between the clinical relapse and remission groups, remaining significantly associated with clinical relapse. LCI findings, including an orange-like color lesion, have diagnostic implications for predicting the risk of clinical relapse in UC during the 1-year follow-up period.